ANALISIS PRODUKTIVITAS TENAGA KERJA TERHADAP PEKERJAAN KERAMIK PADA PANDEMI COVID-19 - Safri Safri; Azzahra Nursantyendo Putri; I Ketut Sucita (KERN, 2022)
Ceramic work is one of the finishing works in construction projects. During the Covid-19 pandemic, construction projects in Indonesia experienced an impact in the form of a slowdown in work and even a temporary cessation of work , including ceramic work. Although ceramic work is an indoor job, Covid-19 has an effect on labor productivity which is part of the delay in construction projects. In construction projects, labor productivity will have an impact on the compatibility between the planned implementation schedule and the actual work progress in the field. Unsupervised labor productivity can hinder work. The productivity of the workforce can be influenced by several factors, such as human resources, weather, work methods, managerial, and COVID-19 health protocols. There are only a few articles that discuss the influence of Covid-19 on labor productivity work in finishing work, especially ceramic work. The purpose of this study was to determine the level of productivity of ceramic work workers during the Covid-19 pandemic and to find out the comparison of the influence of the factors that influence it. This study uses the Work Sampling method to measure the level of labor productivity because it does not need to be monitored continuously, does not require large costs, and does not give much disturbance to workers. The research was conducted by observing the work directly in the field, distributing questionnaires, and interviewing. The results showed that the productivity of ceramic work workers during the pandemic had an average LUR of 70.65% with the most influential factor being the human resource factor. This is indicated by the average value obtained on the human resources variable, which is 24.85. There is a significant average difference between human resource factors and other factors, indicated by the significance value obtained from hypothesis testing is less than 0.05.